"I'll poke you. You'll poke me!" Self-disclosure, social attraction, predictability and trust as important predictors of Facebook relationships - Pavica Sheldon (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2009)
The purpose of this research was to test how social attraction on Facebook influences self-disclosure, predictability, and trust in another individual. Results of a survey of 243 students showed that we tell our personal secrets on Facebook to those that we like. Although many nonverbal cues are absent on Facebook, its users still perceive a high predictability of their Facebook friends’ behavior. Facebook users have very little uncertainty about the behavior of the person to whom they intimately self-disclose to. Our findings support Uncertainty Reduction Theory – the more Facebook users talk, the less uncertainty they experience (Axiom 1) and are able to like each other more. The more certain they are about their behavior, the more they trust them, and the more they trust them, the more they disclose to them.